Genes expression by using cDNA Microarray in Whallak-tang - Cheol-kyung Sin; Chae-woo Lee; Sun-ae Yoo; Hyoun-min Youn; Kyung-jeon Jang; Choon-ho Song; Chang-beohm Ahn; Cheol-hong Kim (Korean Pharmacopuncture Institute, 2008)
Objective : This study was undertaken to determine the effect of Whallak-tang on expression of CD/cytokine Genes. Methods : The expression of CD/Cytokine Genes were examined by cDNA microarray using the human mast cell line(HMC-l). Results : The expression of ATP5F1, FLJ20671, unknown, KIAA0342, OAS2, unknown genes were increased in 200~300% range. The expression of unknown, MDS006, IFITM1, MRPL3, ZNF207, FTH1, FBP1, NRGN, NR1H2, KIAA0747 genes were decreased in 0~33% range. Conclusion : These results would provide important basic data on the possibility of the clinical treatment of Whallaktang in musculoskeletal disease.